Navigating cooperative marketplaces: the Chumash Indians and the dynamics of hunting/gathering/fishing economies - Gamble, Lynn H. (Frontiers in Human Dynamics, 2025)
The Chumash Indians from Southern California produced, used, and traded shell beads for approximately 8,000–10,000 years. Their exchange network included an extensive portion of Western North America. Many scholars recognize that some shell beads from the region were used as currency starting at least 1,500 years ago. Substantial evidence for the production and use of these beads exists in the Santa Barbara Channel region, allowing researchers to investigate a hunting/gathering/fishing group’s use of money in marketplaces. The Chumash Indians used money for purchasing food, ceremonial paraphernalia, and other items at open marketplaces during ritual gatherings with groups of southern California Indians from diverse cultural and linguistic backgrounds. The focus of the paper is to assess a non-state society to determine if its marketplace strategies are based on self-serving actors who do not promote cooperation, or if the participants create and maintain institutions to inhibit overexploitation and depletion of resources, therefore fostering cooperation. On the basis of ethnohistoric, ethnographic, and archeological data, I propose that among the Chumash, participants in their marketplaces organized and maintained institutions that furthered cooperation. The Chumash created hybrid spaces at their ritual gatherings where strategies such as altruistic punishment, market management, regular marketplace periodicity, and established marketplace locales served to promote cooperation. Understanding non-state societies that had an emphasis on trade networks and economic structures such as the Chumash is one means in revisiting past interpretations of premodern societies that traditionally were viewed as lacking marketplace exchange.